Klazomenaı Yüzey Araştırmaları (Klasp) - Koparal, Elif (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
Klazomenai Survey Project (KLASP), initiated in 2006 in the Urla-Çeşme peninsula (İzmir) is a regional survey project combined extensive and intensive survey, remote sensing and geo-archaeological research. The project is aimed at providing a diachronic understanding of settlement patterns within the rural territories of poleis located on the peninsula, which are Klazomenai, Teos, Lebedos and Erythrai. Although the core aim of the research is investigating the rural landscapes around the Ionian poleis, it has an expanded approach and methodology to provide a more holistic understanding of the cultural landscape. KLASP documents all sorts of archaeological evidence and cultural heritage from Paleolithic to Ottoman period for defining the settlement patterns for macro periods and explaining how the cultural landscapes were formed, evolved and transformed within their natural environment on the peninsula. In a broader sense, the project aims at integrating the peninsula with ancient Aegean networks. So far the field surveys documented various types of cultural landscape features such as settlements, forts, watch-towers, border marks, agricultural terraces, tumuli. The project makes use of the evidence to define ritual landscape, defensive network and settlement patterns, and seeks the socio-cultural and environmental dynamics that caused the shifts in settlement systems.